Sports integrities: A conceptual and methodological framework for analysis and policymaking - McNamee, M.; Moriconi, M. (Sport, Ethics and Philosophy, 2025)
Since the manipulation of sport competitions became one of the main threats to sport integrity, both the academy and international organizations have sought to establish a coherent conceptual framework that defines what criteria determine a manipulation and what are the factors that might cause it. Although the literature has shown that the manipulation of sport competition is a multifaceted phenomenon that includes individual, relational, organizational and institutional variables, most of the authors have focused their explanations on individual factors, and institutional prevention campaigns continue to understand match-fixing as a problem of moral failure of on-field sports actors. This work proposes a novel dynamic framework for analysis based on the theoretical roots on Morin’s paradigm of complexity and Archer’s critical realism. In addition to articulating the micro, meso, and macro factors together, the paper defends the idea of three conceptions of integrity, personal, competition and institutional, often operating simultaneously in the same space. Each one of these integrities, operates across individual, organizational and structural levels, acting recursively on the others, generating the gears of the global sports integrity. We then discuss the reasons, structures, opportunities and incentives that each of these integrities creates and fuels. We argue that the errors and ineffectiveness of the fight against the manipulation of sport competitions are largely due to a lack of understanding of, and appreciation for, the different conceptions of integrity and their interactions that require different approaches and differentiated public policies. We conclude with innovative possibilities for more effective policy-making processes in this space.